Polymerized human cord hemoglobin assisted with ascorbic acid as a red blood cell substitute alleviating oxidative stress for blood transfusion - Kong, Weichen; Zhou, Wentao; He, Zeng; Zhang, Xuejun; Li, Shen; Zhong, Rui; Liu, Jiaxin (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Blood transfusion is widely used in clinical settings, where considerable efforts have been devoted to develop red blood cell substitutes to overcome blood shortage and safety concerns. Among the several kinds of artificial oxygen carriers, hemoglobin-based oxygen carriers are promising due to their inherent good oxygen-binding and -loading properties. However, difficulties in prone to oxidation, production of oxidative stress, and injury in organs limited their clinical utility. In this work, we report a red blood cell substitute composed of polymerized human cord hemoglobin (PolyCHb) assisted with ascorbic acid (AA) that alleviates oxidative stress for blood transfusion. Methods: In this study, the in vitro impacts of AA on the PolyCHb were evaluated by testing the circular dichroism, methemoglobin (MetHb) contents and oxygen binding affinity before and after the addition of AA. In the in vivo study, guinea pigs were subjected to a 50% exchange transfusion with PolyCHb and AA co-administration, followed by the collection of blood, urine, and kidney samples. The hemoglobin contents of the urine samples were analyzed, and histopathologic changes, lipid peroxidation, DNA peroxidation, and heme catabolic markers in the kidneys were evaluated. Results: After treating with AA, there was no effect on the secondary structure and oxygen binding affinity of the PolyCHb, while the MetHb content was kept at 55%, which was much lower than that without AA treating. Moreover, the reduction of PolyCHbFe3+ was significantly promoted, and the content of MetHb could be reduced from 100% to 51% within 3 h. In vivo study results showed that PolyCHb assisted with AA inhibited the formation of hemoglobinuria, upgraded the total antioxidant capacity and downgraded the superoxide dismutase activity of kidney tissue, and lowered the expression of biomarkers for oxidative stress, e.g., malondialdehyde (ET vs ET+AA: 4.03±0.26 μmol/mg vs 1.83±0.16 μmol/mg), 4-hydroxy-2-nonenal (ET vs ET+AA: 0.98±0.07 vs 0.57±0.04), 8-hydroxy 2 deoxyguanosine(ET vs ET+AA: 14.81±1.58 ng/ml vs 10.91±1.36 ng/ml), heme oxygenase 1 (ET vs ET+AA: 1.51±0.08 vs 1.18±0.05) and ferritin (ET vs ET+AA: 1.75±0.09 vs 1.32±0.04). The kidney histopathology results also demonstrated that kidney tissue damage was effectively alleviated. Conclusion: In conclusion, these comprehensive results provide evidence for the potential role of AA in controlling oxidative stress and organ injury in the kidneys induced by PolyCHb, and suggest that PolyCHb assisted with AA has promising application for blood transfusion.